2020
DOI: 10.1183/23120541.00275-2019
|View full text |Cite
|
Sign up to set email alerts
|

Repeat assessment of examination signs among children in Malawi with fast-breathing pneumonia

Abstract: BackgroundAs part of a randomised controlled trial of treatment with placebo versus 3 days of amoxicillin for nonsevere fast-breathing pneumonia among Malawian children aged 2–59 months, a subset of children was hospitalised for observation. We sought to characterise the progression of fast-breathing pneumonia among children undergoing repeat assessments to better understand which children do and do not deteriorate.MethodsVital signs and physical examination findings, including respiratory rate, arterial oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Up to 7% of patients may develop intercostal retractions during periodic monitoring. 21 Other authors have used automatic respiratory rate counters; however, they are not universally available and require cost-effectiveness studies. 22 23 It has also been previously shown that the sensitivity and specificity of caregivers is insufficient to recognise tachypnoea and signs of respiratory distress in respiratory diseases and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 7% of patients may develop intercostal retractions during periodic monitoring. 21 Other authors have used automatic respiratory rate counters; however, they are not universally available and require cost-effectiveness studies. 22 23 It has also been previously shown that the sensitivity and specificity of caregivers is insufficient to recognise tachypnoea and signs of respiratory distress in respiratory diseases and pneumonia.…”
Section: Discussionmentioning
confidence: 99%